Foreword From Editor - 13th Edition - Andri Yatmo, Yandi (ASEAN Journal of Community Engagement, 2023)
The current AJCE edition brings together meaningful discussions of community engagement programs as ways to disseminate various skills towards better society livelihood, focusing on product-making skills, women-led soft skills for families, and marketing skills. Elaborating on these objectives, this issue consists of four research-based articles and three case-based articles. The authors of this edition come from the background of economy, chemistry, community, psychology, and education—enabling diverse understanding of skills for the community and the means of how these skills can be acquired from different knowledge backgrounds.